Investigating the Cyclical Properties of World Trade - Monika Ruschinski (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2006)
The world economy in the last two decades is clearly marked by the integration of emerging countries in the international division of labor. To better understand the globalization effect, it is helpful to analyze the pattern and structure of world trade volume in the past, in order to draw conclusions for future development. An unobserved components model is used for decomposing world trade volume into trend, cycle, seasonal and irregular components. The analyses show that the process of the world trade volume is driven by the well-known fluctuations in form of the Kitchin and Juglar Cycle. Furthermore, there is one more cycle with a period between 4 and 5 years which improves the estimation results significantly. The information of the cyclical behavior of the time series is used for projections.
Keywords: F02; F17; 330; World trade; economic integration; unobserved components model; forecasting